Non-Human Animals as Resources for Political Communication During War: The Case of Ukraine. - Holmberg, Arita; Ortega Zepeda, Javiera (Journal of War & Culture Studies, 2025)
In this article, we direct attention to how non-human animals are used as resources for political communication in war. The analysis explores how this practice comes to be used in war communication and how it can be conceptualized as political animal capital. We apply a visual methodology in combination with reflexive thematic analysis. The empirical material consists of non-human animals' pictures, videos, and illustrations and was retrieved from the Instagram account "Ukraine.ua". The material covers one year, from the start of the Russian invasion of Ukraine on February 24th, 2022. The results show that non-human animals are represented in political communication in four ways: As war victims, as diplomats, as war heroes/emergency workers, and as fundraisers. We conclude that using non-human animals as resources for political communication in war means they produce an additional form of animal capital to the ones previously discussed in the literature.